Tolstoy’s Philosophic System and Taoism - Lu Venya (Obrazovanie i Nauka, 2015)
Due to the intensive economic growth and consumer society formation, there expands a view that the human life value depends mainly on the material benefits and money; meanwhile, the moral values trail behind leading the humanity towards the spiritual crisis. The author recommends addressing the heritage of our great ancestors and studying both the works of L. N. Tolstoy and Taoism philosophy in order to maintain the spiritual self and revive our faith in human powers. Taoism is the native law of the world’s order demonstrating the natural ways of life, developing the harmonious life style, and teaching the natural control methods in compliance with the laws of nature.For the most Russian and Chinese readers Lev Tolstoy is a great writer and thinker; his philosophic system being one of the most significant in the Russian spirituality and ideology. L. Tolstoy rejected the western rationalism and studied the Chinese philosophic and religious doctrines. The author conducted a comparative analysis of Tolstoy’s concepts (non-resistance to evil by violence, wise non- doing) and Taoism key concepts, and makes a conclusion about their organic interrelations, and the influence of the Chinese wisdom on Tolstoy’s works and worldview.